CHH DNA methylation increases at 24‐PHAS loci depend on 24‐nt phased small interfering RNAs in maize meiotic anthers. Issue 5 (12th December 2020) - Zhang, Mei; Ma, Xuxu; Wang, Chunyu; Li, Qing; Meyers, Blake C.; Springer, Nathan M.; Walbot, Virginia
Summary: Plant phased small interfering RNAs (phasiRNAs) contribute to robust male fertility; however, specific functions remain undefined. In maize ( Zea mays ), male sterile23 ( ms23 ), necessary for both 24‐nt phasiRNA precursor (24‐ PHAS ) loci and Dicer‐like5 ( Dcl5 ) expression, and dcl5‐1 mutants unable to slice PHAS transcripts lack nearly all 24‐nt phasiRNAs. Based on sequence capture bisulfite‐sequencing, we find that CHH DNA methylation of most 24‐ PHAS loci is increased in meiotic anthers of control plants but not in the ms23 and dcl5 mutants. Because dcl5‐1 anthers express PHAS precursors, we conclude that the 24‐nt phasiRNAs, rather than just activation of PHAS transcription, are required for targeting increased CHH methylation at these loci. Although PHAS precursors are processed into multiple 24‐nt phasiRNA products, there is substantial differential product accumulation. Abundant 24‐nt phasiRNA positions corresponded to high CHH methylation within individual loci, reinforcing the conclusion that 24‐nt phasiRNAs contribute to increased CHH methylation in cis .